SYSTEMATIC LITERATUR RIVIEW : IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Mohammad Erihadiana; Tsania Nurfadillah; Farid Abdul Majid; Ahmad Rifa’i (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to systematically review the results of research on the implementation of the Merdeka Curriculum in Islamic Religious Education (PAI) in Indonesia. The method used is a Systematic Literature Review (SLR) of ten national scientific articles published between 2020 and 2024. The results of the study show that the Merdeka Curriculum provides flexibility for teachers to design learning that is in accordance with the characteristics and needs of students, as well as encouraging the creation of a contextual, reflective learning process that is oriented towards strengthening religious values, morals, and Al-Qur'an literacy. This curriculum also emphasizes the importance of forming a Pancasila student profile through a project approach and experience-based learning. However, its implementation still faces several obstacles, such as teachers' limited understanding of the concept of differentiated learning, a lack of supporting facilities, and a lack of professional guidance. Therefore, it is necessary to strengthen teachers' capacity through continuous training, collaboration between educators, and the optimization of learning technology in line with Islamic values.